Hubungan Bauran Pemasaran dengan Keputusan Pembelian Produk Biji Kopi Robusta Harap Kopi di Kota Tangerang - Sinaga, Apri Gunawan; Yuliawati, Yuliawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The phenomenon of Indonesian lifestyle integrating coffee as a part of social activities, along with the stagnation of loyal customers at Harap Kopi since 2021, forms the background of this study. This research aims to analyze the relationship between the marketing mix—which includes product, price, place, and promotion—and the purchase decision of robusta coffee beans in the home industry of Harap Kopi in Tangerang City. A quantitative approach with a descriptive correlational method and convenience sampling technique was employed, involving 50 respondents. The data were analyzed using Spearman’s rank correlation. The results indicate that all marketing mix variables have a positive and significant relationship with purchase decisions. Price (r = 0.653) and promotion (r = 0.641) variables show a strong correlation, while product (r = 0.444) and place (r = 0.401) show a moderate correlation.